Malaysia Islamic Finance Global Hub: A Comparative Study Towards The Assessment Bodies In Reporting Global Hub Countries - Mohd Nazri Mohd Noor; Mohammad Noorizzuddin Nooh; Asmaddy Haris; Muhammad Ridhwan Ab. Aziz; Azrul Azlan Bin Iskandar Mirza; Joni Tamkin Bin Borhan; Patmawati Binti Ibrahim (Center For Promoting Ideas (CPI), USA, 2024)
International Journal of Business and Social Science Vol. 5, No. 9; August 2014